Compliance of temozolamide with concurrent radiotherapy as an adjuvant in patients with high grade glioma – a retrospective study - Ramanan, V. Arun; Jeeva, S.; Sowmiya, KR. (Publishing Office of the University of Rzeszow, 2023)
Introduction and aim. High grade glioma is the most aggressive form of primary brain tumour with a median survival of one year. Maximal safe resection followed by temozolamide-based concurrent chemoradiation and adjuvant chemotherapy is the standard of care. To assess the compliance of temozolamide in patients of high-grade glioma who underwent concurrent chemoradiation followed by adjuvant chemotherapy Material and methods. 30 patients of high grade glioma diagnosed and treated in our Oncology department during the period of March 2016 to March 2018 were analyzed retrospectively. Cases included in this study were patients with biopsy proven high grade glioma who underwent maximal safe surgery, temozolamide-based concurrent chemoradiation, followed by adjuvant chemotherapy with temozolamide. Data regarding age, gender, histopathology, extent of surgery, performance status, radiotherapy dose, chemotherapy cycles and treatment toxicity profiles were recorded. Results. Treatment was generally well tolerated with most patients experiencing grade 1 and 2 toxicities, which were managed with supportive care. Grade 3 toxicities were noted as follows: anaemia (6.7%, n=2), neutropenia (16.7%, n=5) and thrombocytopenia (16.7%, n=5). Treatment with TMZ was discontinued in 6.7% (n=2) of individuals due to myelosupression. No grade 4 hematological toxicities were observed in the study group. Conclusion. The compliance of temozolamide in high grade gliomas is high with less treatment interruptions and manageable side effect profile.
Ethical approval was obtained from the Institutional ethical committee, Government Stanley Medical College and hospital (ECR/131/Inst/TN/2020/RR-21).
Keywords: glioblastoma multiformae; high grade gliomas; radiotherapy; temozolamide